Analisis Faktor Penyebab Kesulitan Memecahkan Masalah Matematika Materi Pecahan Berdasarkan Gaya Belajar Siswa Kelas VI SDN Bogem - Boby Waluyo Purna Irawan; Sri Surachmi W; Sumaji Sumaji (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the factors causing the difficulty of solving math problems with fractions based on learning styles. This research uses qualitative research method with content analysis design and case study type. The subjects in this study were 3 students in class VI SDN Bogem with each learning style. The research subject selection technique used in this study was purposive sampling. Data collection techniques used questionnaires, in-depth interviews, participant observation, and documentation. The data analysis was carried out through data reduction, data presentation, and drawing conclusions. The validity of the data used source triangulation, technical triangulation, and time triangulation. The results of this study indicate that the factors that cause students to have difficulty solving mathematical problems with fractions based on learning styles are: 1) students do not understand the language in sentences so that students do not know the meaning of the questions given, 2) students find it difficult to change from story questions to math sentences. , 3) lack of mastery of various strategies in solving problems, 4) students are not accustomed to solving problem solving problems, 5) lack of accuracy and caution in performing arithmetic operations, 6) students do not understand the concept of fractional material.